The Effect of Friction Coefficient in Thermal Analysis of Friction Stir Welding (FSW) - Meyghani, B. (Institute of Physics Publishing, 2019)
The process of Friction Stir Welding (FSW) can be deeply investigated with the help of finite element modelling. In reality, the friction coefficient would decrease, because as the temperature rises the material becomes softer and weaker. However, past studies often presumed that the friction coefficient is a constant value, a presumption which consequently led to a disparity between the reality and the simulated model. This paper investigates the effect of applying temperature dependent and constant friction coefficient values to thermal behaviour during FSW. The comparisons between different models was done, and it was shown that the achieved temperature is affected by the friction coefficient. After comparing the results of models with results from experiments, it is concluded that the model in which temperature dependent values were applied is the most realistic one. Â© Published under licence by IOP Publishing Ltd.